Adelmidrol + sodium hyaluronate in IC/BPS or conditions associated to chronic urothelial inflammation. A translational study. (August 2018) - Ostardo, Edoardo; Impellizzeri, Daniela; Cervigni, Mauro; Porru, Daniele; Sommariva, Monica; Cordaro, Marika; Siracusa, Rosalba; Fusco, Roberta; Gugliandolo, Enrico; Crupi, Rosalia; Schievano, Carlo; Inferrera, Antonino; et al.
Graphical abstract: Abstract: Interstitial cystitis/painful bladder syndrome (IC/PBS) is a chronic bladder condition characterized by frequent urination, bladder inflammation and pain. It is a particular challenging disease and a clear unmet medical need in terms of identifying new therapeutic strategies. The aim of study was to evaluate the anti-inflammatory effects of intravesical Vessilen ® (a new formulation of 2% adelmidrol (the diethanolamide derivative of azelaic acid) + 0.1% sodium hyaluronate) administration in rodent models of IC/BPS and in IC/BPS patients or other bladder disorders. Acute and chronic animal models of cystitis were induced by a single or repetitive intraperitoneal injections of cyclophosphamide (CYP); patients with IC/BPS or with bladder pain syndrome associated with symptoms of the lower urinary tract treated once weekly by bladder instillation of Vessilen ® for 8 weeks. CYP instillation caused macroscopic and histological bladder alterations, inflammatory infiltrates, increased mast cell numbers, bladder pain, increased expression of nitrotyrosine, decreased expression of endothelial tight junction zonula occludens-1. Intravesical Vessilen® treatment was able to ameliorate CYP induced bladder inflammation and pain by inhibiting nuclear factor-κB pathway and inflammatory mediator levels as well as reduced mechanical allodynia and nerve growth factor levels. A significant improvement in quality of life and symptom intensity were evident in patients with IC/BPS or other bladder disorders treated with Vessilen ® . Vessilen ® could be a new therapeutic approach for human cystitis.